PUTUSAN HAKIM TINDAK PIDANA KORUPSI YANG TIDAK BERDASARKAN DENGAN PERMA NOMOR 1 TAHUN 2020 PADA PENGADILAN NEGERI PONTIANAK - Diocto, Pniel Destenesse; Ismawati, Sri; Hertini, Mega Fitri; Siagian, Parulian; Aswandi, Aswandi (Faculty of Law, Universitas Tanjungpura, 2023)
Abstract One form of law enforcement is the imposition of punishment on the defendant which is reflected in the judge's decision. Especially in the trial of corruption crimes since Law Number 31 of 1999 concerning the Eradication of Corruption Crimes was enacted, most corruption defendants are required to use Article 2 and Article 3 of the Corruption Law concerning acts of enriching/benefiting oneself or another person or a corporation that can detrimental to state finances. The decision of the Corruption Court against the Defendants who violated Articles 2 and 3 of the Corruption Eradication Law, there is a very striking disparity. To overcome this disparity, the Supreme Court of the Republic of Indonesia has issued Perma Number 1 of 2020 concerning Guidelines for the Criminalization of Article 2 and Article 3 of the Corruption Eradication Law which was promulgated in the State Gazette on July 24, 2020. The panel of judges who tried case Number 25/Pid.Sus-TPK/2021/PN.Ptk only considered Perma Number 1 of 2020 as a guideline, not seeing the Perma as a procedural law whose existence is a product of legislation that fills legal voids and shortcomings and bind the judge's freedom in imposing a sentence even though the meaning of the judge's freedom is to be free to make decisions without any intervention from internal and external parties and judges in deciding cases are still guided by the applicable laws, so that the freedom of judges is not absolute freedom but must be responsible. Because Perma Number 1 of 2020 is a product of legislation that fills legal voids and deficiencies, the judge in imposing a criminal offense under Article 2 and Article 3 of the Law on the Eradication of Criminal Acts of Corruption is obliged to follow the Regulation of the Minister of Justice Number 1 of 2020 as a procedural law and needs to be There are strict sanctions from the institutional leadership of the Supreme Court of the Republic of Indonesia against judges who impose criminal penalties on Article 2 and Articles of the Law on the Eradication of Criminal Acts of Corruption, which do not comply with the Perma. Abstrak Salah satu bentuk penegakan hukum adalah penjatuhan hukuman kepada terdakwa yang tercermin dalam putusan hakim. Khusus dalam persidangan tindak pidana korupsi sejak Undang-Undang Nomor 31 Tahun 1999 Tentang Pemberantasan Tindak Pidana Korupsi diberlakukan, kebanyakan terdakwa korupsi dituntut menggunakan Pasal 2 dan Pasal 3 Undang-Undang Tipikor tentang perbuatan memperkaya/menguntungkan diri sendiri atau orang lain atau suatu korporasi yang dapat merugikan keuangan negara. Putusan Pengadilan Tindak Pidana Korupsi terhadap Terdakwa yang melanggar Pasal 2 dan Pasal 3 UU Pemberantasan Tindak Pidana Korupsi, terdapat disparitas yang sangat mencolok. Untuk mengatasi adanya disparitas tersebut Mahkamah Agung Republik Indonesia telah mengeluarkan Perma Nomor 1 Tahun 2020 Tentang Pedoman Pemidanaan Pasal 2 Dan Pasal 3 Undang-Undang Pemberantasan Tindak Pidana Korupsi yang telah diundangkan dalam Lembaran Negara pada tanggal 24 Juli 2020. Majelis hakim yang mengadili perkara Nomor 25/Pid.Sus-TPK/2021/PN.Ptk hanya menganggap Perma Nomor 1 Tahun 2020 sebagai pedoman saja bukan melihat Perma tersebut sebagai hukum acara yang keberadaannya merupakan produk perundang-undangan yang mengisi kekosongan dan kekurangan hukum dan mengikat kebebasan hakim dalam menjatuhkan pemidanaan padahal arti kebebasan hakim tersebut adalah bebas menjatuhkan putusan tanpa ada intervensi dari pihak internal dan eksternal dan hakim dalam memutus perkara tetaplah berpedoman kepada perundang-undangan yang berlaku, sehingga kebebasan hakim bukanlah kebebasan yang mutlak melainkan harus bertanggungjawab. Oleh karena Perma Nomor 1 Tahun 2020 yang keberadaannya merupakan produk perundang-undangan yang mengisi kekosongan dan kekurangan hukum, maka hakim dalam menjatuhkan pidana Pasal 2 dan Pasal 3 Undang-Undang Pemberantasan Tindak Pidana Korupsi wajib mempedomani Perma Nomor 1 Tahun 2020 sebagai hukum acara dan perlu ada sanksi tegas dari pimpinan institusi Mahkamah Agung Republik Indonesia terhadap hakim yang menjatuhkan pidana Pasal 2 dan Pasal Undang-Undang Pemberantasan Tindak Pidana Korupsi yang tidak mempedomani Perma tersebut.